Legal consequences of the caregiver's death in a life care contract - Vukotić Miloš (Anali Pravnog Fakulteta u Beogradu)
Serbian Succession Act provides that the position of a caregiver in a life care contract may be inherited only by their descendants and spouse. If other persons succeed the caregiver, or if descendants or spouse refuse to provide care, the contract is rescinded by operation of law. The right to compensation for received care is provided only if descendants or spouse have a justified reason for refusing to provide care. This article contains a critical analysis of this solution. The author shows that the restriction of heritability is too narrow, that the issue of compensation is inadequately resolved, and that the interests of care recipient are endangered because they cannot influence the fate of the contract. The author proposes a solution of unlimited heritability with the right of both parties to rescind the contract. The reasons for rescission would be taken into account when the issue of compensation is decided.